A dynamic weaving simulator for filament-level 3D woven fabric modelling. (7th November 2022) - Ma, Ying; Xiang, Weihong; Lu, Sheng; Hu, Hanjie; Zeng, Xianjun
A dynamic textile weaving simulator is established to connect weaving actions to fabric patterns and microstructures. It utilizes the Digital Element Approach (DEA) under the framework of the software package Digital Fabric and Composite Analyser (DFCA). The key components of a Jacquard loom are explicitly modelled utilising the 'hole/no hole' principle. Yarn interlacing motion is guided by weaving matrix specified by steps. Shedding, weft insertion, beat-up, and take-up actions are modelled and explained. The inter-fibre contact force, fibre forces (tensile, shear, and bending), and boundary conditions in the weft direction are considered. The weaving process of five cells in the warp direction of a 10-layer 3D orthogonal woven fabric is simulated at the filament level to derive for its microstructure. The results show that the fabric microstructure continues to change after being woven, and the thickness and length of each individual cell decrease with further weaving steps. The microstructures of newly woven cells converge after the weaving of two further cells in the lengthwise direction. The microstructure of the second cell closely matches that of an actual weaved fabric, as evaluated by microscopy images. Penetration occurs between adjacent weft yarns in the same column, which fundamentally changes their microstructure, composition, and material properties. Parametric studies show that the ratio of binder to warp yarn tension determines the fabric thickness. Increases in the take-up length and binder yarn tension lead to a decrease and increase in the reed tension, respectively. This work provides valuable insights into fabric design and manufacture instruction.